Exploring Societal Fears of Aging and Loss of Beauty in Disney Film “Tangled” and Indian Film “Yashoda”: A Feminist Film Analysis - Bhuvaneswari Gopalakrishnan; Rashmi Rekha Borah; Subbu Lakshmi M. (Галактика медиа: журнал медиа исследований)
The fear of aging and the loss of beauty is a pervasive societal issue that transcends cultural boundaries, often manifesting in the media and film industry. This paper examines the 2010 animated film “Tangled” and an Indian Film “Yashoda” (2022) through a feminist lens, focusing on the themes of fears of aging and loss of beauty. It analyses how the antagonists, Gothel (Tangled) and Madhubala (Yashoda) navigate their journey in maintaining their beauty and youth which is a stereotypical expectation of the society. This study examines the portrayal of societal fears regarding aging and the loss of beauty through a feminist lens in the Disney film “Tangled” and the Indian film “Yashoda.” Both films, while culturally distinct, navigate the complex terrain of beauty standards, aging, and female autonomy. “Tangled” presents the narrative of Rapunzel, whose magical hair symbolizes youth and beauty, coveted by the antagonist, Mother Gothel, to prevent her own aging. This dynamic serves as a metaphor for the societal obsession with youth and the lengths to which individuals will go to preserve beauty.